2021
DOI: 10.24251/hicss.2021.163
|View full text |Cite
|
Sign up to set email alerts
|

Gamification of Sustainable Consumption: a systematic literature review

Abstract: As awareness about the need to shift current individual consumption practices towards more sustainable ones grows, broader sets of methods are being sought to encourage sustainable lifestyles, gamification being one of the most notorious due to its application via apps and other technology-related solutions. Building upon an intention-impact approach, this review used practice-theory to analyze academic literature addressing gamification approaches to shift individual consumption practices into more sustainabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…The interviewees were selected from the apps in the database created for a systematic review of gamified consumption apps in 2021 (Guillen M. et al, 2022). These apps were clustered in four groups, facilitating the selection of 52 apps, as shown in Table 1.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interviewees were selected from the apps in the database created for a systematic review of gamified consumption apps in 2021 (Guillen M. et al, 2022). These apps were clustered in four groups, facilitating the selection of 52 apps, as shown in Table 1.…”
Section: Data Collectionmentioning
confidence: 99%
“…Gamified apps feature a series of elements and mechanics that induce gameful experiences within the system (Koivisto & Hamari, 2019). What previous research on gamification and sustainable consumption showed (Guillen Mandujano et al, 2021), is a prevalence of nine gamification elements applied across approaches designed to address sustainable consumption. These are goals and missions, points, leaderboards and rankings, badges, social media features like sharing and tagging, rewards, progress bars and levels, reputation systems, and avatars.…”
Section: Organizational Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another research focuses on improving the collaboration between team members to deliver optimal outcomes in teamwork [16]. They present a framework to assist in Based on existing research on game element categories and game types [17]- [19] and research on most used game elements in gamification [20], we selected some game types and game elements that have the potential to improve the interpersonal dynamic in usability testing. Table 1 shows a preliminary analysis of how they might apply in usability testing scenarios.…”
Section: Literature On Gamificationmentioning
confidence: 99%
“…In the frame of The European project UrbanWaste (2016-2019) [1], IDeTIC developed a gamified mobile application (WasteApp) to stimulate RB in visitors to tourist cities with high seasonality, concluding that it managed to encourage RB and improve the reputation of the destination when implemented (Guillen et al , 2021; Aguiar-Castillo et al , 2019).…”
Section: Introductionmentioning
confidence: 99%